Contrasts and positions in information structure - Kučerová, Ivona; Neeleman, Ad. (Cambridge : Cambridge University Press, 2012)
Sažetak: "Information structure, or the way the information in a sentence is 'divided' into categories such as topic, focus, comment, background, and old versus new information, is one of the most widely debated topics in linguistics. This volume incorporates exciting new work on the relationship between syntax and information structure. The contributors are united in rejecting accounts that assume designated syntactic positions associated with specific information-structural interpretations, and aim instead to derive information-structural conditions on word order and other phenomena from the way syntax and syntax-external systems interact. Beyond this shared aim, the authors of the various chapters advocate a number of approaches, based on different types of data (syntactic, semantic, phonological/phonetic) from a range of languages. The book is aimed at specialists in syntax and/or information structure, as well as students and linguists in related fields keen to familiarise themselves with current issues in this fascinating area of research".
Sadržaj: 1. Introduction / Ivona Kučerova and Ad Neeleman; Part I. The Architecture of Grammar and the Primitives of Information Structure: 2. Predicate integration: phrase structure or argument structure? / Daniel Büring; 3. Wh-intonation and information structure in South Kyeongsang Korean and Tokyo Japanese / Hyun Kyung Hwang; 4. Grammatical marking of givenness / Ivona Kučerova 5. Interface configurations: identificational focus and the flexibility of syntax / Balazs Suranyi; 6. Focus and givenness: a unified approach / Michael Wagner; 7. The locality of focusing and the coherence of anaphors / Edwin Williams; Part II. Exploring the Interfaces: Case Studies: 8. NP ellipsis without focus movement/projections: the role of classifiers / Artemis Alexiadou and Kirsten Gengel; 9. Focus in Greek wh-questions / Theodora Alexopoulou and Mary Baltazani; 10. Against FocusP: arguments from Zulu / Lisa Lai-Shen Cheng and Laura J. Downing; 11. Scrambling as formal movement / Gisbert Fanselow; 12. Left peripheral arguments and discourse interface strategies in Yucatec / Maya Stavros Skopeteas and Elisabeth Verhoeven; References.
Sadrži bibliografske bilješke i kazalo.
Keywords: garamatika - opća i poredbena -- sintaksa; kontrastivna lingvistika; fokus (lingvistika)